Metaphor as a way to explore subtle elements of school culture: "a school unlike any other" in a student metaphor - research report - Urszula Dernowska; Joanna Górecka; Aleksandra Tłuściak-Deliowska (Journal of Modern Science, 2023)
Objectives Metaphor can be a tool of knowing the culture of the organization. It can be used to diagnose and improve the organization, including the school. Transferring ideas about the school to other objects allows researchers to reach subtle elements of school culture which resist quantitative approaches, hence the intention to include metaphorical analysis in scientific investigations focused on the culture of the school of alternative education. The article presents a fragment of research material collected as part of a team project aimed at empirical recognition and comparison of cultures of selected non-public primary schools – schools "other than all".